2022
DOI: 10.1093/hr/uhac138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UDP-rhamnosyltransferases and UDP-galactosyltransferase involved in flavonol glycosylation inMorella rubra

Abstract: Flavonol glycosides are health-promoting phytochemicals important for human nutrition and plant defence against environmental stresses. Glycosylation modification greatly enriches the diversity of flavonols. Morella rubra, a member of the Myricaceae, contains high amount of myricetin 3-O-rhamnoside (M3Rha), quercetin 3-O-rhamnoside (Q3Rha), and quercetin 3-O-galactoside (Q3Gal). In the present study, MrUGT78R1 and MrUGT78R2 were identified as two functional UDP-rhamnosyltransferases, while MrUGT78W1 was identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…PpUGT78A2 in group F was identified as a flavonoid 3-O-glycosyltransferase involved in different glycosylation of anthocyanin and flavonol in P. persica (Cheng et al, 2014;Xie et al, 2022). And in M. rubra, four UGT members in group F, i.e., MrUGT78R1, MrUGT78R2, MrUGT78W1, and MrUFGT in the present study, were identified as flavonoid 3-O-glycosyltransferases involved in accumulation of diverse flavonoid glycosides (Ren et al, 2022).…”
Section: Mrufgt and Mrugt72b67 Involved In Flavonoid Glucosylationsupporting
confidence: 59%
See 4 more Smart Citations
“…PpUGT78A2 in group F was identified as a flavonoid 3-O-glycosyltransferase involved in different glycosylation of anthocyanin and flavonol in P. persica (Cheng et al, 2014;Xie et al, 2022). And in M. rubra, four UGT members in group F, i.e., MrUGT78R1, MrUGT78R2, MrUGT78W1, and MrUFGT in the present study, were identified as flavonoid 3-O-glycosyltransferases involved in accumulation of diverse flavonoid glycosides (Ren et al, 2022).…”
Section: Mrufgt and Mrugt72b67 Involved In Flavonoid Glucosylationsupporting
confidence: 59%
“…Enzymatic activity assay was carried out as reported with some modifications ( Ren et al, 2022 ). Reactions were performed in a total volume of 100 μl mixture containing 0.1 M Tris–HCl buffer (pH 7.5), 1 mM sugar donors (UDP-Glc/UDP-Gal/UDP-Rha), 60 μM sugar acceptors (Q/C), and 1–2 μg recombinant proteins at 30°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations